SPIRITUAL LEADERSHIP IN HIGHER EDUCATION: A CONCEPTUAL REVIEW TOWARD A VALUE-BASED FRAMEWORK - Putu Gede Subhaktiyasa (Jurnal Manajemen Pendidikan (JMP), 2026)
Spiritual leadership is considered to have a positive impact on organisational sustainability, but its understanding remains limited to higher education institutions. This study aims to examine and broaden the understanding of value-based spiritual leadership in higher education institutions. The research uses a qualitative approach with a narrative literature review design. The analysis is conducted thematically and through critical conceptual synthesis of spiritual leadership, organisational values, and educational management. The findings identify five dimensions of spiritual leadership in higher education institutions: vision, hope/faith, altruistic love, soulful Directive, and organizational inclusivity. These dimensions emphasize the importance of moral reflection and structural justice in the diversity and complexity of higher education institutions. An understanding of this fosters spiritual wellbeing through a multidimensional approach that encompasses personal, communal, environmental, and transcendental aspects. The model shapes holistic spiritual leadership in higher education. Higher education management needs to build value-based spiritual leadership that is reflective, humanistic, and transformative.